Normative data of the Spanish version of the Montreal Cognitive Assessment (MoCA) in older individuals from Peru - Lucia Bulgarelli; Emilia Gyr; Jose Villanueva; Koni Mejía; Claudia Mejía; Renato Paredes; Sheyla Blumen (Dementia & Neuropsychologia)
ABSTRACT. The Montreal Cognitive Assessment (MoCA) has proven to be an effective tool for detecting early dementia in older adults. However, in the Latin American region, there are few available norms of the Spanish version. The Peruvian population faces major healthcare barriers to early screening, so it is important to validate this instrument within this population. Objective: To standardise the Spanish version of the MoCA for the older population in Lima, addressing the critical need for culturally and demographically adapted cognitive evaluation tools in Peru. Methods: The test was administered to 338 ambulatory and homebound adults aged 60 to 80 (216 women) from three institutions: San Miguel District Municipality, San José Obrero Polyclinic in Barranco, and EDMECON in Surco. we computed regression-based norms adjusted for age and education. Results: Sex was not a predictor of the total scores of MoCA. Moreover, age (R2=0.12) and education (R2=0.24) significantly influenced cognitive performance, with education being the strongest predictor. A raw score above 18 indicates normal cognitive performance for the total sample. Conclusions: We provided normative data and cutoff scores for older Peruvians, supporting the clinical use of the MoCA in Peru and setting a benchmark for future test standardizations in the region.